Ana María Barrenechea, fundadora de objetos críticos - Marcela Croce (Cuadernos LIRICO)
A method for organizing literary criticism in Argentina is to notice the definition of objects that fulfills every critic. Ana María Barrenechea (1913-2010) began the practice in 1953 when she published a text on Macedonio Fernández who installed him as a key figure in the local literature. That inaugural decision continued a few years later with Borges. The probably more canonical writer of the Western literature in the second half of the twentieth century was set as a critical object in 1957 with La expresión de la irrealidad en la obra de Borges. After that came Cuaderno de bitácora de Rayuela, followed by the attention to Ricardo Piglia in narrative and Susana Thénon in poetry. Without neglecting the Latin American scopes of her literary interests, explicit especially from the 70s, to acknowledge Barrenechea as the person who established the more proliferating objects of study of the Argentine criticism, constantly changing and updating her work, is a task that still needs to be performed.